An efficient low-temperature triethylamine gas sensor based on 2D ultrathin SnO2 nanofilms. (16th November 2021) - Liu, Yuchang; Liu, Hongjie; Hu, Anjie; Wei, Yingmei; Ou, Wenchao; Deng, Xianwang; Wang, Shaopeng; Yu, Kefu
Abstract: The quest to develop inexpensive chemical sensing materials that are energy-efficient, portable, and with efficient performance lies at the center of next-generation sensor development. Owing to their low cost, easy preparation, high response, and smooth integration with electronic circuits, metal oxide semiconductors have received particular attention. Yet, metal oxide semiconductor based sensors often suffer from high power consumption due to their high operating temperature, which hinders them from practical applications. To solve this problem, herein, we proposed ultrathin sub-4 nm SnO2 films synthesized by a facile tunable hydrothermal method. Benefiting immensely from its two-dimensional anisotropic nature, the proposed SnO2 ultra-thin film exhibits a large specific area of 94.41 m 2 g −1 and possesses surface oxygen vacancies. The obtained sample was practically applied as a gas sensor; the results indicate that the ultra-thin SnO2 film based sensor exhibits the highest sensitivity to triethylamine (19.2 at 100 ppm), outstanding repeatability, and excellent sensing selectivity at a low working temperature of 150 °C.